The theory of global value chains and global commodity chains: automotive industry in Turkey - Dinçer, Mehmet Alper (My University, 2007)
Küresel ekonomi geçtiğimiz on yıllarda pek çok açıdan önemli bir dönüşüm geçirdi ve ekonomik aktivitelerin ulusal sınırlar arasındaki derin olmayan coğrafi dağılımı yerini işlevsel olarak bütünleşmiş uluslararası yayılmış aktivitelere bıraktı. Bu süreçte küresel ekonomide karşılıklı bağımlılık önemli ölçüde arttı ve bu döneme uluslararası ticaret, yatırım ve finans damgalarını vurdular. Çok uluslu şirketlerce organize edilen bu derin bütünleşme ulusal sınırlar için imalat sanayilerinin yeniden incelenmesi ihtiyacını doğuracak biçimde mallara sınır ötesi değer katan aktiviteleri içermektedir. 1980’lerden beri Türkiye kademeli olarak bu bütünleşme sürecine dâhil olmaktadır ve Türkiye’deki imalat sanayileri az veya çok küresel imalat sanayi ile bütünleşmektedir. Bu geçmiş on yıllar süresince Türkiye’de otomotiv sanayi devam eden kapasite artırımları ve imalat sanayi ihracatında yükselen payı ile öne çıkmaktadır. Bu tez Türkiye’nin küresel ekonomi ile bütünleşmesinde otomotiv sanayinin rolünü değerlendiriyor ve Türkiye’deki otomotiv sanayinde daha fazla katma değerli imalat üretimi ve ihracatının yapılıp yapılmadığını sorguluyor.

The global economy has transformed in very important ways during the past several decades and the mere extension and geographical spread of economic activities across national border is replaced by functional integration of internationally dispersed activities. During this period of time interconnectedness of global economy vastly increased while international trade, investment and finance have become the hallmark of this change. This profound integration mainly organized by TNCs encompasses the manufacturing of goods in cross border value adding activities which conducts to the need of re-analyzing manufacturing processes within national borders. Since 1980s Turkey gradually takes part in this transformation process of global economy and manufacturing industries in Turkey more or less integrate into global manufacturing industries. Throughout these past decades automotive industry in Turkey stands out with its ongoing capacity expansions and ascending share in manufactured exports. This dissertation evaluates automotive industry’s role in Turkey’s integration to global economy and questions the emergence of a more value added manufacturing and export regarding automotive industry in Turkey.
Keywords: Ekonomik Bütünleşme; Global Değişim; Küresel Ekonomi; Türkiye_Ekonomi